Knowledge, Attitude and Behavior on Halal Pharmaceutical Among Residents in East Jakarta - Wiyati, Tuti; Nugrahaeni, Fitria; Lestari, Puja; Rahayu, Yayuk; Wulandari, Nora (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: The guarantee of the halalness of a product has been regulated in Indonesian Law. However, there are still many drugs circulating without including halal certification.Objectives: The purpose of this study was to assess knowledge, attitude and behaviour on halal pharmaceutical of people in East Jakarta.Methods: This study conducted using cross-sectional method with snow-ball sampling. Data was collected through online using developed questionnaire in google-form. Univariate analysis was done to present the frequency of each characteristic as well as the level of knowledge, attitudes and behaviour of the respondents. Bivariate analysis using Spearman-Rho test conducted to obtain the correlation between variables.Results: A count of 800 respondents participated in this study with more than three-quarters was identified has good knowledge (77.0%), positive behaviour (99.2%) and good behaviour (79.8%) toward halal pharmaceutical. The knowledge and attitude as well as knowledge and behaviour were significantly correlated (p-value <0.05) with positive direction (r 0.088 and r 0.262, respectively).Conclusion: The result of the study showed a positive respond from respondents on halal pharmaceutical. This might be occurred because the research was conducted in the big city where they have more possibility to be exposed to the information about halal products, including halal pharmaceutical.